2020
DOI: 10.1158/0008-5472.can-20-0865
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Systematic Functional Analysis to Benchmark an In Silico Framework Distinguishes Driver from Passenger MEK Mutants in Cancer

Abstract: Despite significant advances in cancer precision medicine, a significant hurdle to its broader adoption remains the multitude of variants of unknown significance identified by clinical tumor sequencing and the lack of biologically validated methods to distinguish between functional and benign variants. Here we used functional data on MAP2K1 and MAP2K2 mutations generated in real-time within a co-clinical trial framework to benchmark the predictive value of a three-part in silico methodology. Our computational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
3
14
0
1
Order By: Relevance
“…Mutations in MAP2K2 are infrequent in cancer (0.7% of predominantly solid tumors analyzed), found in a variety of tumor types, and spread across the length of the protein. 20 While there is no functional data on the exact missense mutation seen in our patient, a recent comparative study identified MAP2K2…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mutations in MAP2K2 are infrequent in cancer (0.7% of predominantly solid tumors analyzed), found in a variety of tumor types, and spread across the length of the protein. 20 While there is no functional data on the exact missense mutation seen in our patient, a recent comparative study identified MAP2K2…”
Section: Discussionmentioning
confidence: 81%
“…p.R231H as a significant hot spot based on an in silico analysis, although there was no downstream ERK activation in vitro in transfected human embryonic kidney cells to suggest that this alteration is activating. 20 It is unclear if the in vitro data can be extrapolated to signaling in hematopoietic cells in vivo and if a substitution by leucine rather than histidine is comparable in this regard. Thus, while the FIL1L1-RARA fusion is the oncogenic driver, the MAP2K2 mutation suggests that the biology of this patient's malignancy may align in part with JMML, similar to the prior report of a pediatric patient with this fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in MEK and ERK are less studied but have been noted in developmental disorders and in both naturally occurring neoplasms and in response to BRaf inhibitors as a mechanism for resistance when treating cancers such as melanoma [219][220][221][222]. ERK, although often overactive due to abnormal upstream activity, is rarely mutated in cancer [223].…”
Section: Mek and Erk Mutationsmentioning
confidence: 99%
“…Caution should be used in applying single-patient anecdotes to routine cancer care, and putative biomarkers identified by exceptional responder analyses should be validated within the context of prospective clinical trials (Figure 1). Additionally, it is crucial to recognize that not all mutations in the same gene yield the same biologic phenotype (Chakravarty et al, 2017;Hanrahan et al, 2020). Furthermore, the pattern of co-alteration, tumor lineage, interaction with the host immune system, and other factors, many of which are not easily assayed using current methods, are also critical in modulating therapeutic responses.…”
mentioning
confidence: 99%